Alanine-substituted mutant on Gly373 and Asn375 of Cry1Ai-h-loop 2 causes reduction in both toxicity and binding against Helicoverpa armigera - Yu-xiao LIU; Zi-shan ZHOU; Ge-mei LIANG; Fu-ping SONG; Jie ZHANG (Journal of Integrative Agriculture, 2019)
Cry1Ai-h-loop 2 is a mutant of Cry1Ai constructed by exchanging loop 2 from Cry1Ah protein and shows insecticidal activity against Helicoverpa armigera. The toxicity of Cry1Ai-h-loop 2, in contrast to the very low toxicity of Cry1Ai, is closely associated with the eleven residues in the loop 2 region. To characterize the key sites of loop 2 in Cry1Ai-h-loop 2, alanine-substituted mutants were generated. The toxicity of these mutants against H. armigera indicated that dual-mutant on Gly373 and Asn375 caused a significant decrease in toxic activity. ELISA binding and competition binding assays demonstrated that the reduction of toxicity in the mutant of interest was correlated with decreased binding affinity.